2009
DOI: 10.1039/b822065b
|View full text |Cite
|
Sign up to set email alerts
|

Reaction mechanisms : Part (ii) Pericyclic reactions

Abstract: This report surveys the 2008 literature on mechanisms of pericyclic reactions. A recurring theme in this year's reports is again catalysis. Several studies addressed the acceleration of pericyclic reactions by electron transfer, protonation, encapsulation-induced preorganization and selective transition state stabilization via hydrogen bonding or Lewis acid complexation. In addition, the mechanisms of a variety of pericyclic reactions leading to interesting polycycles were examined in detail, and several cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 76 publications
0
3
0
Order By: Relevance
“…Previous literature suggests that the MPW1K and B3LYP functionals provide accurate description of the activation barriers for [1,5]­H-shift reactions for cyclopentadiene and Z -1,3-pentadiene derivatives though the MPWIK functional seems to describe tunneling corrections better. , However, the MPW1K functional is found to overestimate the barrier for 6π-electrocyclization. On the other hand, the B3LYP functional has been shown to reproduce the experimental reaction barriers reliably for several pericyclic reactions including 6π-electrocyclization in bicyclo[4.2.0]­octa-2,4-diene derivatives. , , Fry has investigated valence tautomerization in a series of substituted 1,3,5-cyclooctatriene into the corresponding bicyclooctadienes and it can be found that B3LYP/6-31G­(d) level of theory reasonably reproduce the experimental barrier and reaction energy for 1,3,5-cyclooctatriene ( 5a ) (see Scheme S1 in Supporting Information). Although they recommended CBS-QB3 level of theory as the superior choice for these set of compounds, high computational cost restricts its application.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous literature suggests that the MPW1K and B3LYP functionals provide accurate description of the activation barriers for [1,5]­H-shift reactions for cyclopentadiene and Z -1,3-pentadiene derivatives though the MPWIK functional seems to describe tunneling corrections better. , However, the MPW1K functional is found to overestimate the barrier for 6π-electrocyclization. On the other hand, the B3LYP functional has been shown to reproduce the experimental reaction barriers reliably for several pericyclic reactions including 6π-electrocyclization in bicyclo[4.2.0]­octa-2,4-diene derivatives. , , Fry has investigated valence tautomerization in a series of substituted 1,3,5-cyclooctatriene into the corresponding bicyclooctadienes and it can be found that B3LYP/6-31G­(d) level of theory reasonably reproduce the experimental barrier and reaction energy for 1,3,5-cyclooctatriene ( 5a ) (see Scheme S1 in Supporting Information). Although they recommended CBS-QB3 level of theory as the superior choice for these set of compounds, high computational cost restricts its application.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the B3LYP functional has been shown to reproduce the experimental reaction barriers reliably for several pericyclic reactions including 6π-electrocyclization in bicyclo[4.2.0]octa-2,4-diene derivatives. 25,[39][40][41][42][43]53 Fry has investigated valence tautomerization in a series of substituted 1,3,5-cyclooctatriene into the corresponding bicyclooctadienes and it can be found that B3LYP/6-31G(d) level of theory reasonably reproduce the experimental barrier and reaction energy for 1,3,5-cyclooctatriene (5a) (see Scheme S1 in Supporting Information). 43 Although they recommended CBS-QB3 level of theory as the superior choice for these set of compounds, high computational cost restricts its application.…”
Section: ■ Computational Detailsmentioning
confidence: 99%
See 1 more Smart Citation